High-performance elastocaloric materials for the engineering of bulk- and micro-cooling devices. (11th April 2018) - Frenzel, Jan; Eggeler, Gunther; Quandt, Eckhard; Seelecke, Stefan; Kohl, Manfred
Abstract: Abstract : Pseudoelastic NiTi-based shape-memory alloys (SMAs) have recently received attention as candidate materials for solid-state refrigeration. The elastocaloric effect in SMAs exploits stress-induced martensitic transformation, which is associated with large latent heat. Most importantly, cyclic mechanical loading/unloading provides large adiabatic temperature drops exceeding 25 K at high process efficiencies. This article summarizes the underlying principles, important material parameters and process requirements, and reviews recent progress in the development of pseudoelastic SMAs with large coefficients of performance, as well as very good functional fatigue resistance. The application potential of SMA film and bulk materials is demonstrated for the case of cyclic tensile loading/unloading in prototypes ranging from miniature-scale devices to large-scale cooling units.